Effects of heterologous platelet-rich plasma gel on standardized dermal wound healing in rabbits - Abegão,Karina Gomes Barros (2015)
PURPOSE: To evaluate the potential of heterologous platelet-rich plasma (PRP) gel for surgical skin wound healing in rabbitsMETHODS: Blood from a single healthy dog was used for PRP production, with calcium gluconate added to the PRP to form the gel. Two surgical excisions, one to the right and the other to the left of the dorsal midline, were made in six rabbits. One side was randomly allocated to topical application of a physiological solution, and the other was allocated to treatment with heterologous PRP gel. Clinical assessments (weight, pain sensitivity, coloring, edema, hyperemia, exudation, crust, and granulation) and morphometric evaluations were performed 0, 3, 7, 10, 14, and 17 days postoperatively. Histological analysis was performed on the 17th day.RESULTS: With the exception of the presence of a crust at day 10, clinical variables did not differ significantly between the experimental groups. In both the control and PRP-treated groups, differences were identified when comparing time-points in terms of wound area reduction. Histological results indicated no significant differences between the control group and the PRP-treated group.CONCLUSION: Heterologous platelet-rich plasma gel promoted dermal wound healing in rabbits with no adverse effects.